On the problem and algorithms for coordinated optimal management of production and material flows of an enterprise - Mezentsev, Y A; Baranova, N V; Pavlov, P S (Journal of physics. Conference series, 2020)
The paper presents the problem of controlling the input and output material flows of an industrial enterprise, supplemented by the condition for the choice of sales prices and adjusted in terms of the number of products sold. This economic and mathematical model finds optimal solutions for the management problem at enterprises, namely, the problem of forming a production program according to the criterion of the maximum net profit at the end of the planning period. In the constraints of the model, both production components and constraints on resources and the logic of input and output material flows are systematically taken into account. The considered model and the given control problems are investigated using a unified approach that allows working with logical conditions of any complexity and setting the corresponding formal optimization problems. The results of testing the algorithm on test data close to industrial (real) dimensions are also given.